The Influence of Physics Teachers' Learning Methods on Learning Outcomes in Students - Setyaningsih, Naomi; Kapah, Silmi; Apriliyani, Rizka; Silalahi, Nathan Alexander; Ardila, Dede; Fadilah, Yourie; Maulana, Fajar; Elisabeth, Anggi; Utami, Indri Sari (CV. Dharma Samakta Edukhatulistiwa, 2025)
This study aims to analyze the differences in physics learning outcomes between students who are taught with game-based learning, experimental, and cooperative learning methods. The research method used a pseudo-experimental design with three treatment groups. Participants consisted of 33 students in class X who were given 3 learning method treatments: game-based learning, experimentation, and cooperative learning. Data was collected through learning outcome tests and interviews with teachers and students. Statistical analysis using one-way ANOVA showed a very significant difference between the three methods (F=53.03; p=3.06E-16). The highest average learning outcomes were achieved by the game-based learning group (81.82), followed by experimentation (87.58), and cooperative learning (93.3). The results of the interviews revealed that the experimental method was preferred by students because it was interactive and contextual. This study concludes that the selection of innovative learning methods in accordance with the characteristics of the material can significantly improve students' physics learning outcomes.